AVALIAÇÃO DA ATIVIDADE ANTI-INFLAMATÓRIA DE JUSTICIA NODICAULIS (NEES) LEONARD EM MODELOS AGUDOS EM CAMUNDONGOS (CIPEEX, 2026)
INTRODUCTION: Species of the genus Justicia are used in folk medicine against inflammatory processes, but Justicia nodicaulis is still poorly studied. OBJECTIVE: This study aimed to evaluate the anti-inflammatory activity of the ethanolic extract of J. nodicaulis (EEJN) in an acetic acid (1.2% i.p.)-induced abdominal writhing model in Swiss mice. MATERIALS AND METHODS: EEJN was obtained using Soxhlet extraction with absolute ethanol. For the pharmacological evaluation, Swiss mice were orally treated with EEJN (500 mg/kg), vehicle (Tween 80 2%), or indomethacin (10 mg/kg). After 60 minutes, they received acetic acid (1.2% i.p.), and the abdominal writhing responses were recorded for 30 minutes. RESULTS: EEJN reduced abdominal writhing from 105 ± 20.4 (vehicle) to 80.8 ± 25.6 (EEJN), but without statistical significance (p = 0.204), while indomethacin reduced writhing by 60% (42.0 ± 15.6; p = 0.003). CONCLUSION: EEJN may present anti-inflammatory potential at higher doses, and further studies using concentrations such as 1 g/kg are recommended.